GLOBAL NEWS FLOW DEBATE IN THE ERA OF SOCIAL MEDIA NETWORKS: IS THE U.S MEDIA STILL THE WORLD’S NEWS LEADER? - Ekeanyanwu, Nnamdi T.; Jnr., Yusuf Kalyango; Peters, Ada Sonia (European Scientific Journal, ESJ, 2012)
The News Flow Debate (NFD), which is about the imbalance in the flow of news internationally, has continued to generate interest in communication research. This is because the issues that gave birth to the debate in the first instance have remained fluid, notwithstanding the impact of social media on the unidirectional flow of news and information due to the liberalization and proliferation of the newsgathering and dissemination processes at the grassroots level. This study analyzes the content of U.S. media coverage to determine the impact of social media on the content and flow of news in the United States. In other words, this study hopes to find if traditional media organizations in the U.S. are still setting public agenda in the era of social media networks popularity.